On the hydrography of Denmark Strait - Mastropole, Dana M.; Pickart, Robert S.; Valdimarsson, Héðinn; Våge, Kjetil; Jochumsen, Kerstin; Girton, James B. (Journal of Geophysical Research: Oceans, 2017)
Author Posting. © American Geophysical Union, 2017. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research: Oceans 122 (2017): 306–321, doi:10.1002/2016JC012007. Using 111 shipboard hydrographic sections across Denmark Strait occupied between 1990 and 2012, we characterize the mean conditions at the sill, quantify the water mass constituents, and describe the dominant features of the Denmark Strait Overflow Water (DSOW). The mean vertical sections of temperature, salinity, and density reveal the presence of circulation components found upstream of the sill, in particular the shelfbreak East Greenland Current (EGC) and the separated EGC. These correspond to hydrographic fronts consistent with surface-intensified southward flow. Deeper in the water column the isopycnals slope oppositely, indicative of bottom-intensified flow of DSOW. An end-member analysis indicates that the deepest part of Denmark Strait is dominated by Arctic-Origin Water with only small amounts of Atlantic-Origin Water. On the western side of the strait, the overflow water is a mixture of both constituents, with a contribution from Polar Surface Water. Weakly stratified “boluses” of dense water are present in 41% of the occupations, revealing that this is a common configuration of DSOW. The bolus water is primarily Arctic-Origin Water and constitutes the densest portion of the overflow. The boluses have become warmer and saltier over the 22 year record, which can be explained by changes in end-member properties and their relative contributions to bolus composition. US National Science Foundation (RP and DM) Grant Number: OCE-0959381; ;Norwegian Research Council Grant Number: 231647 (KV) 2017-07-20